Предмет: Математика,
автор: adiletkabil20
3a+3b - (a-2b-(a+b)-(a-b)+2b-2a)+3b помогите пожалуйста
Ответы
Автор ответа:
0
3a+3b-(a-2b-a-b-a+b+2b-2a)+3b=3a+6b-3a=6b
Автор ответа:
0
3a+3b - (a-2b-(a+b)-(a-b)+2b-2a)+3b= 3a+3b-a+2b+a+b+a-b-2b+2a+3b= (3a-a+a+a+2a)+(3b+2b+b-b-2b+3b)=6a+6b=6*(a+b)
Похожие вопросы
Предмет: Математика,
автор: KudryavtsevNikita
Предмет: Литература,
автор: Vanea20032003
Предмет: Биология,
автор: Kvartenell
Предмет: Химия,
автор: 55liz
Предмет: Литература,
автор: lolkekchebyrek8676